Development of ESD E-Modules for Students' Ecoliteracy and Critical Thinking: Pengembangan E-Modul ESD untuk Ekoliterasi dan Berpikir Kritis Siswa - Diki Akmal Wildan; Dadang Jaenudin; Deddy Sofyan S. (Academia Open, 2025)
General Background: The integration of technology into education has revolutionized learning, enabling more interactive, flexible, and student-centered approaches. Specific Background: However, the use of E-Modules to foster ecological literacy and critical thinking within the framework of Education for Sustainable Development (ESD) remains underexplored. Knowledge Gap: Despite ESD's alignment with Indonesia’s Merdeka curriculum, empirical evidence on E-Modules addressing ESD objectives is limited, especially at the elementary level. Aims: This study aims to develop and evaluate the effectiveness of an ESD-based E-Module focused on preserving local natural resources in enhancing elementary students’ ecoliteracy and critical thinking. Results: Utilizing the ADDIE model within a pre-experimental design, the E-Module demonstrated high validation scores from experts (average 97.5%), strong student (83%) and teacher (82%) responses, and a high N-Gain score (0.706) for both ecoliteracy and critical thinking improvements. Novelty: The novelty lies in the contextual integration of local environmental content into a digital learning format grounded in ESD principles. Implications: The findings indicate that the E-Module is both effective and feasible, providing an innovative, sustainable tool for primary education that promotes critical environmental awareness and thinking skills from an early age.Highlight : E-Module development enhances student ecoliteracy and critical thinking using the ADDIE model. Validation and N-Gain results show high effectiveness and feasibility for classroom use. The innovation addresses the lack of ESD-integrated learning tools in elementary schools. Keywords : E-Module, ESD, Ecoliteracy, Critical Thinking, Elementary Education